2019
DOI: 10.1002/nau.23922
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms 7 years after the first delivery: Correlation to the mode of delivery

Abstract: Objective To investigate the extent of lower urinary tract symptoms (LUTS) during pregnancy and 7 years after birth in primipara and their association with delivery mode history and other factors. Methods A longitudinal cohort study was conducted in 12 hospitals representative of the diversity of the seven administrative regions of China. Of 10 098 women recruited at the third trimester, 3862 (38.25%) responded at 1 year, and 1115 (11.04%) responded at 7 years. A modified Chinese Bristol Female Lower Urinary T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The modality of past deliveries may impact development of nocturia currently because some delivery methods can impact the lower urinary tract more significantly in the long term. 2,14 Nevertheless, previously pregnant patients had a greater odds of nocturia than nulligravida patients, in agreement with past findings, 13 demonstrating that pregnancy can have long-term impacts on LUTS.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…The modality of past deliveries may impact development of nocturia currently because some delivery methods can impact the lower urinary tract more significantly in the long term. 2,14 Nevertheless, previously pregnant patients had a greater odds of nocturia than nulligravida patients, in agreement with past findings, 13 demonstrating that pregnancy can have long-term impacts on LUTS.…”
Section: Methodssupporting
confidence: 86%
“…Pregnancy is associated with significant hormonal and physical changes and has been implicated in the development of lower urinary tract symptoms (LUTS) including nocturia, frequency, urinary incontinence (UI), urgency, incomplete bladder emptying, straining, and voiding difficulty 1 . Although most of these symptoms seem to resolve after delivery, some may persist for months or years 2 . Of these LUTS, nocturia, defined as waking up ≥2 times to void as per the International Consultation on Incontinence Research Society 2018 definition, 3,4 is reported as the most common symptom and has a significant effect on quality of life during gestation; nevertheless, the association between nocturia and pregnancy is less characterized than the relationship between pregnancy and other LUTS 5–7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings in terms of the relationship between LUTS and older age, obesity, number of pregnancies, and number of vaginal deliveries correspond to previous findings. [ 6 7 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…For some women, postpartum LUTS are temporary, but a considerable number of postpartum women experience long-term issues. A longitudinal cohort study [3] revealed that the incidence of maternal urge urinary incontinence (UUI) and stress urinary incontinence (SUI) increased from 5.7% and 29.9% during pregnancy to 22.8% and 46.4% at 1 year after delivery and 10.2% and 23.7% at 7 years after delivery, respectively. Thus, early effective therapies are clearly needed to prevent and treat postpartum LUTS.…”
Section: Introductionmentioning
confidence: 99%